Pelatihan Pemanfaatan E-learning Moodle dalam Mengeksplorasi Asynchronous Learning di MA Diniyah Putri Pekanbaru - Estika Satriani; Syafriyani Nofitri; Resy Oktadela; Destry Pryanti Kadar (Pusat Riset dan Inovasi Nasional, 2025)
The Community Service Program (PkM) implemented at MA Diniyyah Putri Pekanbaru aimed to improve teachers' capacity in utilizing the Moodle Learning Management System (LMS) as a learning tool, particularly in implementing asynchronous learning models. This activity employed a participatory approach with three core stages: planning, implementation, and evaluation. During the planning stage, the implementation team conducted observations and interviews to identify teachers' needs and challenges in using learning technology. The implementation stage then focused on delivering materials, hands-on practice using Moodle, and intensive mentoring in designing asynchronous learning content tailored to students' needs. Evaluation of the program was conducted through a questionnaire with 20 participating teachers, which provided an overview of the training's effectiveness. The results showed a significant improvement in teachers' abilities in compiling digital materials, managing virtual classes, giving assignments, and monitoring students' online learning activities. Teachers also began to be able to design asynchronous learning that was more interactive and flexible, and encouraged students' independent learning. Another visible impact was the increased creativity of teachers in utilizing Moodle features to support distance learning. These findings align with previous studies that emphasize Moodle's superiority in supporting digital learning while strengthening the professionalism of educators. This training is expected to foster a relevant and sustainable technology-based professional development model, particularly in Islamic boarding schools and similar educational institutions. This will enable teachers to be more adaptable to the challenges of the digital era and able to provide meaningful learning experiences for students. These findings align with previous studies that emphasize Moodle's superiority in supporting distance learning and enhancing teacher creativity. This training is expected to serve as a model for technology-based teacher professional development in Islamic boarding schools and similar educational institutions.